Optimizing MRI-guided prostate ultrasound ablation therapy using retrospective analyses and artificial intelligence - Wright, Cameron (fi=Turun yliopisto|en=University of Turku|, 2023)
Magnetic resonance imaging (MRI)-guided transurethral ultrasound ablation (TULSA) is an emerging therapy that has been used to treat prostate cancer (PCa). TULSA destroys prostate tissue with heat using therapeutic ultrasound. The heating is monitored in real-time using MRI thermometry. Despite TULSA’s promise, there are several challenges that have slowed its widespread adoption. Fortunately, MRI images and heating parameters from all TULSA treatments are stor ed. By conducting detailed retrospective analyses and applying deep learning on existing treatments, we can extract valuable information and then leverage this knowledge to optimize future TULSA treatments. One major challenge occurs for those patients who had PCa radiation therapy failure and are seeking salvage treatment with TULSA. Many of these patients have leftover metal markers in the prostate. These markers can hamper subsequent TULSA therapy because they introduce susceptibility artifacts in the MRI image and may also block the ultrasound, which may compromise treatment safety and efficacy. Through an extensive retrospective analysis, we have determined that gold markers tend not to affect the treatment outcome, except when located simultaneously close to the urethra and far from the target boundary, or when located directly on the target boundary itself. Clinically, gold markers had no apparent effect on treatment safety and efficacy compared to a control cohort without markers at the 12-month follow-up. Conversely, nitinol markers are generally problematic for TULSA. A second major challenge applies to all TULSA treatment indications. Immediately after TULSA therapy, MRI contrast agents are used to visualize the non-perfused volume, an objective measure of the ablation outcome. Unfortunately, even if undertreatment is observed, retreatment is not possible, forcing an additional treatment several months later, and with it the associated risks of a second intervention. By training a deep learning model with existing TULSA treatment-day, contrast-free MRI image sets, we have predicted the non-perfused volume with an accuracy comparable to modern-day deep learning prostate segmentation methods. Overall, this work will help daily clinical practice and increase the odds of a successful TULSA therapy.

MRI-ohjatun eturauhasen ultraääniablaatiohoidon optimointi retrospektiivisten analyysien ja tekoälyn avulla Magneettikuvaus(MRI)-ohjattu virtsaputken kautta annettu ultraääniablaatio (TULSA) on uusi primaarin ja sädehoidon jälkeen paikallisesti uusiutuneen eturauhassyövän (PCa) hoitomuoto. Menetelmässä eturauhaskudosta koaguloidaan korkean intensiteetin ultraäänellä reaaliaikaisessa MRI-ohjauksessa, mikä parantaa hoidon tarkkuutta. Lupaavista kliinisistä tuloksista huolimatta MRI-ohjaus altistaa teknisille ja kliinisille haasteille, mitkä ovat hidastaneet TULSA-hoidon laajempaa käyttöönottoa. TULSA-hoidossa jokainen vaihe rekisteröidään MRI-kuvin. Koneoppimista hyödyntämällä voidaan retrospektiivisesti analysoida näitä MRI-kuvia TULSA-hoitotulosten optimoimiseksi. Sädehoidon ohjauksessa käytetyt eturauhaseen asetetut merkkijyvät saattavat vaikuttaa TULSA-hoidon tehoon ja turvallisuuteen uusiutuneessa PCa:ssä, koska ne voivat aiheuttaa artefaktoja MRI-kuvaan ja estää ultraäänen etenemisen. Laajassa retrospektiivisessa analyysissä todettiin, että kultamerkkijyvät eivät yleensä vaikuta hoitotulokseen, elleivät ne sijaitse samanaikaisesti lähellä virtsaputkea ja kaukana hoitokohteesta tai suoraan kohteen edessä. Kultamerkkijyvillä ei ollut ilmeistä vaikutusta hoidon turvallisuuteen ja tehokkuuteen verrattuna kontrolliryhmään ilman merkkijyviä 12 kuukauden seurannassa. Välittömästi TULSA-hoidon jälkeen hoitotulos varmistetaan merkkiainetehosteisilla MRI-kuvilla, joilla visualisoidaan verenkierroton alue, mikä korreloi akuuttiin kudosvaurioon eli onnistuneeseen hoitovasteeseen. Ongelmana on, että vaikka merkkiainetehosteisissa MRI-kuvissa todettaisiin riittämätön hoitovaste, uudelleenhoito ei ole samalla hoitokerralla mahdollista, koska eturauhaseen kerääntynyt merkkiaine estää hoidon. Tällöin tarvitaan uusi hoitokerta kuukausien kuluttua toimenpiteen sisältämineen riskeineen, mikä viivästyttää hoitoa ja kuormittaa potilasta. Tässä tutkimuksessa onnistuttiin tarkasti ennustamaan verenkierroton alue hoidonaikaisista merkkiainetehostamattomista MRI-kuvista hyödyntämällä syväoppimismallia. Näillä havainnoilla on tärkeä kliininen merkitys TULSA-hoitotulosten parantamisessa.